2017
DOI: 10.1016/j.ymthe.2017.01.017
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long Noncoding RNA LINC00673 Is Activated by SP1 and Exerts Oncogenic Properties by Interacting with LSD1 and EZH2 in Gastric Cancer

Abstract: Long noncoding RNAs (lncRNAs) have emerged as important regulators in a variety of human diseases, including cancers. However, the biological function of these molecules and the mechanisms responsible for their alteration in gastric cancer (GC) are not fully understood. In this study, we found that lncRNA LINC00673 is significantly upregulated in gastric cancer. Knockdown of LINC00673 inhibited cell proliferation and invasion and induced cell apoptosis, whereas LINC00673 overexpression had the opposite effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 37 publications
5
130
0
Order By: Relevance
“…In this study, by retrieving relevant previous reports through the keywords "gastric cancer and RNA," we finally selected four cancer-related protein coding genes, which have been tested by different kinds of experiments. These four genes ("NOV," "KIT," "SP1," and "CLOCK") were considered as seeds in the RWR model [33][34][35][36]. The initial probability P 0 of each seed mRNA was set as 1/n (where n is the number of seed mRNAs), while other non-seed mRNAs were set as 0.…”
Section: Rwr To Prioritize Gc Related Lncrnasmentioning
confidence: 99%
“…In this study, by retrieving relevant previous reports through the keywords "gastric cancer and RNA," we finally selected four cancer-related protein coding genes, which have been tested by different kinds of experiments. These four genes ("NOV," "KIT," "SP1," and "CLOCK") were considered as seeds in the RWR model [33][34][35][36]. The initial probability P 0 of each seed mRNA was set as 1/n (where n is the number of seed mRNAs), while other non-seed mRNAs were set as 0.…”
Section: Rwr To Prioritize Gc Related Lncrnasmentioning
confidence: 99%
“…Importantly, progress in our understanding of CRC can be accelerated by elucidating the regulatory mechanisms involved in CRC carcinogenesis and development. Current evidence has highlighted the roles of long non-coding RNAs (lncRNAs) as crucial modulators in multiple types of tumors, including CRC [4-7]. Thus, novel insights into the involvement of lncRNAs are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…We then investigated the regulatory mechanism of KDM1A in SCAPs. KDM1A has been found to form protein complexes with other proteins during cell proliferation and differentiation . In the present study, we identified several candidate binding partners of KDM1A including PLOD2.…”
Section: Discussionmentioning
confidence: 69%